Aging, Technology and Health - Pak, Richard; McLaughlin, Anne (Elsevier Ltd. : Academic Press, 2018)
Aging, Health and Technology takes a problem-centered approach to examine how older adults use technology for health. It examines the many ways in which technology is being used by older adults, focusing on challenges, solutions and perspectives of the older user. Using aging-health technology as a lens, the book examines issues of technology adoption, basic human factors, cognitive aging, mental health, aging and usability, privacy, trust and automation. Each chapter takes a case study approach to summarize lessons learned from unique examples that can be applied to similar projects, while also providing general information about older adults and technology.